Synergistic Activations of REG Iα and REG Iβ Promoters by IL-6 and Glucocorticoids through JAK/STAT Pathway in Human Pancreatic β Cells - Akiyo Yamauchi; Asako Itaya-Hironaka; Sumiyo Sakuramoto-Tsuchida; Maiko Takeda; Kiyomi Yoshimoto; Tomoko Miyaoka; Takanori Fujimura; Hiroki Tsujinaka; Chikatsugu Tsuchida; Hiroyo Ota; Shin Takasawa (Journal of Diabetes Research)
Reg (Regenerating gene) gene was originally isolated from rat regenerating islets and its encoding protein was revealed as an autocrine/paracrine growth factor for β cells. Rat Reg gene is activated in inflammatory conditions for β cell regeneration. In human, although five functional REG family genes (REG Iα, REG Iβ, REG III, HIP/PAP, and REG IV) were isolated, their expressions in β cells under inflammatory conditions remained unclear. In this study, we found that combined addition of IL-6 and dexamethasone (Dx) induced REG Iα and REG Iβ expression in human 1.1B4 β cells. Promoter assay revealed that a signal transducer and activator of transcription- (STAT-) binding site in each promoter of REG Iα (TGCCGGGAA) and REG Iβ (TGCCAGGAA) was essential for the IL-6+Dx-induced promoter activation. A Janus kinase 2 (JAK2) inhibitor significantly inhibited the IL-6+Dx-induced REG Iα and REG Iβ transcription. Electrophoretic mobility shift assay and chromatin immunoprecipitation revealed that IL-6+Dx stimulation increased STAT3 binding to the REG Iα promoter. Furthermore, small interfering RNA-mediated targeting of STAT3 blocked the IL-6+Dx-induced expression of REG Iα and REG Iβ. These results indicate that the expression of REG Iα and REG Iβ should be upregulated in human β cells under inflammatory conditions through the JAK/STAT pathway.